Casque d'or - Van Parys, Georges 1902-1971 (<<The>> Criterion Coll., 2005)
In an open-air dance hall, the members of Leca's gang are relaxing with their ladies. One of the ladies, Marie, meets Manda, who is a carpenter by trade. Marie's man Roland is a jealous sort and does not like the idea of Marie and Manda becoming friendly, and Leca himself has his eye on Marie. What follows is a story of love, death, friendship and jealousy during the Belle Epoque.
Bildformat: 1.33:1 aspect ratio - New, restored high-definition digital transfer
Orig.: Frankreich 1952
Enth. audio commentary by film scholar Peter Cowie ; 1995 video interview with actor Serge Reggiani ; 1963 video interview with actress Simone Signoret from the French television program "Cinépanorama" ; excerpt from the episode of the French television series "Cinéastes de notre temps" dedicated to Jacques Becker ; rare, silent behind-the-scenes footage of Becker on the set, with commentary by film scholar Philip Kemp ; alternate English-dubbed soundtrack, featuring Signoret, Reggiani, and Claude Dauphin ; new essay by Philip Kemp
Keywords: Geschichte 1900-2000; Halls de danse - France - Drame; Dance halls -- France -- Drama; Gangs -- France -- Drama; Jealousy -- France -- Drama; Man-woman relationships -- France -- Drama; Europa; Frankreich; Europe -- Civilization -- 20th century -- Drama; Feature films; Foreign films, French